2019
DOI: 10.1016/j.sna.2019.111659
|View full text |Cite
|
Sign up to set email alerts
|

Performance comparison of acoustic emission sensor arrays in different topologies for the localization of gas leakage on a flat-surface structure

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The array performance has a large impact on the localization results [ 34 ], so it is necessary to focus on the design of the sensor array. The performance factors affected by the array design mainly include spatial resolution, sidelobe distributions and levels, and spatial aliasing [ 35 ].…”
Section: The Design Of Acoustic Localization Sensormentioning
confidence: 99%
“…The array performance has a large impact on the localization results [ 34 ], so it is necessary to focus on the design of the sensor array. The performance factors affected by the array design mainly include spatial resolution, sidelobe distributions and levels, and spatial aliasing [ 35 ].…”
Section: The Design Of Acoustic Localization Sensormentioning
confidence: 99%
“…For spacecraft, the load needs to be as small and light as possible. Research by Cui et al [16] showed that L-type arrays can obtain the best experimental results with the smallest number of sensors. Therefore, in the following research, an L-shaped array with 8 sensors was used as an example.…”
Section: Delay-and-sum Beamforming Algorithmmentioning
confidence: 99%
“…An important factor affecting the accuracy of ultrasonic localization is the time delay estimation of an ultrasonic signal. The commonly used methods for time delay estimation include: the rising-edge triggering method, the threshold triggering method, basic cross correlation, generalized cross correlation, adaptive filtering, a neural network, deep learning, and so on [ 18 , 19 , 20 , 21 , 22 ]. Among them, the rising-edge trigger method and threshold trigger method are the least computationally intensive methods for time delay estimation, which are generally applicable to the occasions where the waveform profile is clear and has no distortion or small distortion.…”
Section: Introductionmentioning
confidence: 99%